Peer-Mediated Instruction and Academic Outcomes for Students with Autism Spectrum Disorders: A Comparison of Quality Indicators. Issue 5 (19th October 2020) - Haas, April; Vannest, Kimberly; Thompson, Julie L.; Fuller, Marcus C.; Wattanawongwan, Sanikan
ABSTRACT: Schools need cost and resource-efficient strategies to improve the academic performance of students with autism spectrum disorder (ASD). High-quality research demonstrates peer-mediated interventions effects on improved social skills for students with ASD. However, effects of peer-mediated interventions on academic outcomes are less understood concerning quality in ASD populations. This paper provides an updated systematic and quality review of the literature for Peer-Mediated Academic Instruction (PMAI) using peers of students with ASD. Authors identified eight new studies. Evaluation criteria included Council for Exceptional Children's Single Case Design Standards and the What Works Clearinghouse Standards. Results indicate PMAI can be considered and evidence-based practice to improve academic performance in the ASD population. Limitations and future directions are discussed.